PENGARUH PENEMPATAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. BULUH CAWANG PLATATIONS DABUK REJO OGAN KOMERING ILIR - Garaika Garaika; Yansahrita Yansahrita (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2019)
The work ethic in the corporate bureaucracy must still be improved so as to realize optimal performance. In line with this, in an effort to increase employee morale, one of them is by providing motivation, because morale is one of the determining factors in the process of achieving goals. If employee morale begins to decline will result in failure of goals to be achieved, in contrast to high morale, the goals will be achieved properly. The condition that occurs at PT. Buluh Cawang Platations Dabuk Rejo Ogan Komering Ilir is the existence of employee education background constraints that are not appropriate to their line of work. The employees in carrying out work are not supported by their knowledge and expertise which results in suboptimal employee performance. The non-optimal performance of the employee can be seen from not achieving the set work targets. The results of this study want to know the effect of work placement on employee job satisfaction at PT. Buluh Cawang Platations Dabuk Rejo Ogan Komering Ilir. While the analysis tool used is a simple linear regression analysis, and using the t test. This conclusion is obtained partially known work placement (X1) has a significant effect on job satisfaction (Y) at PT. Buluh Cawang Platations Dabuk Rejo Ogan Komering Ilir. This is shown from the t-count value of the work placement variable (X1) = 11.662 which is greater than the t table value of 1.697.